2019
DOI: 10.1111/1759-7714.13175
|View full text |Cite
|
Sign up to set email alerts
|

Soluble fms‐like tyrosine kinase‐1‐enriched exosomes suppress the growth of small cell lung cancer by inhibiting endothelial cell migration

Abstract: Background Previous studies have reported that soluble fms‐like tyrosine kinase‐1 (sFlt‐1) possesses anti‐tumor effects by inhibiting angiogenesis in many cancers. Exosomes can be engineered as delivery vehicles for transferring functional biomolecules, such as proteins, lipids, and nucleic acids (DNA, mRNA, and miRNA) to target cells to affect inflammation, apoptosis, and angiogenesis. The purpose of this study was to investigate whether exosomes can function as efficient carriers of sFlt‐1 in vitro and in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Based on a previous study that showed that soluble FMS-like tyrosine kinase-1 (sFlt-1) exerts anti-tumor activity by suppressing angiogenesis in many cancers, exosomes have been used to load sFlt-1 and tested in both in vitro and in vivo as potential lung cancer therapy. The therapeutic formulation resulted in higher inhibition efficacy on pro-angiogenesis, significant anti-tumor activity via the inhibition of the growth of NCI-H69 tumor xenografts, increased tumor apoptosis, and inhibition of tumor cell proliferation in mice [ 121 ]. Researchers have engineered a drug delivery system consisting of nanosomes, by conjugating gold nanoparticles (GNPs) with the anticancer drug doxorubicin (Dox) and then linking these to the exosome pH-sensitive hydrazone.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Based on a previous study that showed that soluble FMS-like tyrosine kinase-1 (sFlt-1) exerts anti-tumor activity by suppressing angiogenesis in many cancers, exosomes have been used to load sFlt-1 and tested in both in vitro and in vivo as potential lung cancer therapy. The therapeutic formulation resulted in higher inhibition efficacy on pro-angiogenesis, significant anti-tumor activity via the inhibition of the growth of NCI-H69 tumor xenografts, increased tumor apoptosis, and inhibition of tumor cell proliferation in mice [ 121 ]. Researchers have engineered a drug delivery system consisting of nanosomes, by conjugating gold nanoparticles (GNPs) with the anticancer drug doxorubicin (Dox) and then linking these to the exosome pH-sensitive hydrazone.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…miRNAs play an independent role in the pathogenesis and progression of almost all types of cancers, such as non-small cell lung cancer , breast cancer , gastric carcinoma, bladder tumors and may other known tumor types. They are responsible for modulation of their cellular differentiation, as well as in regulating the transcription of their downstream targets [22][23][24][25][26][27][28][29].…”
Section: Ivyspringmentioning
confidence: 99%
“… Enhance angiogenesis [ 29 ] Lung cancer (SCLC) NCI-H69 SCLC cells secreting sFlt-1 HUVECs Exosomes of SCLC cell lines contain very low level of sFlt-1, which significantly increases the migration of HUVECs and weakens the inhibitory effect of NCI-H69-Exo on angiogenesis. Enhance angiogenesis [ 56 ] Lung cancer TECs (derived from ADC and SCC) CDH2; MAPK/ERK and MAPK/JNK signaling pathways Lung cancer patients CDH2 significantly promoted angiogenesis in vivo and in vitro. Enhance angiogenesis [ 57 ] Abbreviations : ADC Adenocarcinoma, CDH2 Cadherin-2, DCs Dendritic cells, HBEs Human bronchial epithelial cells, HUVEC Human umbilical vein endothelial cells, PHD Prolyl hydroxylase, TD-MVs Tumor-derived microvesicles, TECs Tumor-derived endothelial cells, TLR Toll-like receptor, NSCLC Non-small cell lung cancer, SCC Squamous cell carcinoma, SCLC Small cell lung cancer, sFlt-1 Soluble fms-like tyrosine kinase-1, VEGF Vascular endothelial growth factor …”
Section: Introductionmentioning
confidence: 99%
“…Exosomes derived from cells of the SCLC cell line NCI-H69 contain a low level of sFlt-1, which can significantly increase the migration ability of human umbilical vein vascular endothelial cells (HUVECs) and weaken the inhibitory effect of NCI-H69-derived exosomes on angiogenesis. Exosomes rich in sFlt-1 inhibit HUVEC migration induced by NCI-H69-derived exosomes, and thus, may be an effective therapeutic agent for inhibiting SCLC metastasis [ 56 ]. Cadherin-2 (CDH2) expression was significantly elevated in tumor-derived endothelial cells derived from both ADC and squamous cell carcinoma (SCC).…”
Section: Introductionmentioning
confidence: 99%